2018
DOI: 10.1089/lap.2017.0381
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Retroperitoneal Lymph Node Dissection as a Safe Procedure for Postchemotherapy Residual Mass in Testicular Cancer

Abstract: Laparoscopic postchemotherapy RPLND is a feasible, safe, and highly oncologically efficient procedure, which has the benefits of minimally invasive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
1
2
0
1
Order By: Relevance
“…Experiences from a high-volume center [25] comprehensively elaborated the efficacy of this technique, recommending its substitute for O-RPLND despite of the technical challenges. Other reports, including ours, also supported the superiority of L-RPLND over O-RPLND because of their comparable oncological outcomes and a higher morbidity rate of O-ROLND [26,27].…”
Section: Discussionsupporting
confidence: 72%
“…Experiences from a high-volume center [25] comprehensively elaborated the efficacy of this technique, recommending its substitute for O-RPLND despite of the technical challenges. Other reports, including ours, also supported the superiority of L-RPLND over O-RPLND because of their comparable oncological outcomes and a higher morbidity rate of O-ROLND [26,27].…”
Section: Discussionsupporting
confidence: 72%
“…It is difficult to maintain high concentrations of chemotherapies in the pelvic and abdominal lymph nodes, and systemic chemotherapy has little or no treatment effect [7][8][9][10]. Peritoneal hyperthermic perfusion has been used to concentrate drugs locally, and this can augment the antitumor response in retroperitoneal metastatic lymph nodes [11]. However, it is difficult to obtain better results for relatively large retroperitoneal metastatic lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…Retroperitoneal lymph node dissection (RPLND) is recommended for nonseminomatous germ cell tumors (NSGCTs) with a residual mass of over 1 cm after chemotherapy on radiographic imaging according to the European Association of Urology (EAU) guidelines. Previous studies of laparoscopic RPLND (L-RPLND) have shown feasibility but difficulty because of perinodal and perivessel fibrosis and adhesions [2, 3]. Robot-assisted L-RPLND (R-RPLND) has proven its advantages with regard to high-definition three-dimensional visualization, increased freedom of instrument movement, and minimization of tremors.…”
Section: Introductionmentioning
confidence: 99%